Optimized design of asphalt concrete pavement containing phase change materials based on rutting performance. (20th December 2022) - Deng, Yong; Shi, Xijun; Kou, Yan; Chen, Jun; Shi, Quan
Abstract: This paper investigated the effects of phase change materials (PCMs) on temperature field and rutting performance of asphalt concrete (AC) pavement with a focus on PCM types, contents, and locations. To quantify their effects on rut depth accumulation, a pavement finite element (FE) model was constructed with measured material properties and designed structural configuration. The implemented traffic and environmental conditions were obtained from a FE model updating scheme and a heat transfer model with the consideration of traffic speed and the phase change process. Results showed that using polyethylene glycol of 4000 molar mass encapsulated by SiO2 as the PCM to replace 10% of the aggregate in the asphalt top sublayer yielded the best rutting performance; a 14% reduction in the rut depth that was accumulated within one month after pavement construction was predicted for a typical summer case in Texas. This study also revealed that incorporating PCMs into AC does not always lead to pavement rutting performance improvement. This is because (1) the lower thermal conductivity of the PCMs can offset the benefits achieved from the increased heat capacity during phase change, and (2) PCMs will not function if they are added in layers where pavement temperature is not high enough for PCMs to undergo the phase change. Therefore, developing PCMs with higher thermal conductivity together with a judicious selection of PCM types and locations will maximize the effectiveness of the pavement temperature and rutting control.